In vitro and in vivo assessment of magnetically actuated biomaterials and prospects in tendon healing. (May 2016) - Santos, Lívia; Silva, Marta; Gonçalves, Ana I.; Pesqueira, Tamagno; Rodrigues, Márcia T.; Gomes, Manuela E.
Aim : To expand our understanding on the effect of magnetically actuated biomaterials in stem cells, inflammation and fibrous tissue growth.Materials & methods : Magnetic biomaterials were obtained by doping iron oxide particles into starch poly-ϵ-caprolactone (SPCL) to create two formulations, magSPCL-1.8 and 3.6. Stem cell behavior was assessed in vitro and the inflammatory response, subcutaneously in Wistar rats.Results : Metabolic activity and proliferation increased significantly overtime in SPCL and magSPCL-1.8. Electromagnetic fields attenuated the presence of mast cells and macrophages in tissues surrounding SPCL and magSPCL-1.8, between weeks 1 and 9. Macrophage reduction was more pronounced for magSPCL-1.8, which could explain why this material prevented growth of fibrous tissue overtime.Conclusion : Magnetically actuated biomaterials have potential to modulate inflammation and the growth of fibrous tissue.